Differences in the subpopulations of the structural proteins of polyoma virions and capsids: biological functions of the multiple VP1 species. - Bolen, J B (1981)
The structural proteins of polyoma virions and capsids were analyzed by isoelectric focusing and sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Polyoma virion VP1 was found to be composed of six distinct species which had pI's between pH 6.75 and 5.75. Polyoma capsid VP1 was found to contain four species with pI's between pH 6.60 and 5.75. The different forms of virion and capsid VP1 appeared to be generated by modifications (phosphorylation and acetylation) of the initial translation product. The most basic of the virion VP1 species (pI, pH 6.75) was absent in capsids and was found to be exclusively associated with the viral nucleoprotein complex. Three of the virion VP1 species and three of the capsid VP1 species were found in capsomere preparations enriched for hexon subunits. Two VP1 species were specifically immune precipitated from virions with hemagglutination-inhibiting antibodies. These two VP1 species were common to both virions and capsids. Polyoma virions, but not capsids, possessed a single VP1 species which was immune precipitated with neutralizing antibodies. Both virion and capsid VP2 were found to have pI's of approximately pH 5.50. Virion VP3 had a pI of approximately pH 7.00, whereas capsid VP3 had a pI of approximately pH 6.50.